JS06.4.A Intracranial ependymomas of the adult: outcome and response to treatments across molecular subtypes. (5th September 2022) - Bruno, F; Pellerino, A; Pronello, E; Bertero, L; Tampieri, C; Francia Di Celle, P; Mantovani, C; Moro, M; Bartoletti, V; Baciorri, F; Garbossa, D; Soffietti, R; et al.
Abstract: Background: The 2021 WHO Classification lists two molecularly defined types of supratentorial ependymomas (STEs), i.e., ZFTA and YAP1 fusions, and posterior fossa ependymomas (PFEs), i.e, PFA and PFB. Based on retrospective data, the presence of the ZFTA fusion (for STEs) and the PFA subtype (for PFEs) seem to correlate with a poorer outcome. However, prospective data on large cohorts of adult patients are lacking, and the role of treatments is uncertain. The aim of our study is to investigate the clinical characteristics, response to treatment, and outcome of a cohort of adult patients with supratentorial and posterior fossa ependymomas across different molecular subtypes. Patients and Methods: Clinical data of patients ≥18 years with STEs and PFEs were retrospectively collected from 2 Italian Centres (Turin, Treviso). ZFTA and YAP1 fusions were detected by FISH, while PFA and PFB subtypes were defined by anti-H3K27me3 immunohistochemistry. Results: We collected 42 adult patients with STEs (11, 26.2%) and PFEs (31, 73.8%) diagnosed between 1984 and 2021. Median age was 45 years. ZFTA and YAP1 fusions were found in 5 (45.5%) and 1 (9.1%) case of STEs. PFA and PFB subtypes accounted for 9 (29.0%) and 22 (71.0%) cases of PFEs. Extent of resection (EOR) was gross-total (GTR) in 6/11 (54.8%) STEs and 17/31 PFEs (54.8%). 4/11 (36.4%) STEs and 9/31 (29.0%) PFEs received adjuvant radiotherapy (RT). Median progression-free survival (mPFS) and overall survival (mOS) were 172 and 61.6 months for STEs patients, and not reached (NR) and 332 months for PFEs. For patients with STEs, the presence of ZFTA fusion correlated with a significant shorter PFS (64.0 months vs NR, p = 0.05) and with a trend for shorter mOS (168.0 months vs NR, p = 0.307). The only patient with YAP1 fusion had a very long PFS (33 years). In a multivariable analysis, EOR and adjuvant RT did not significantly affect survival of STEs patients.For patients with PFEs, PFA and PFB subtypes did not differ significantly in terms of mPFS (NR vs 137.0 months, p = 0.513) and mOS (NR vs NR, p = 0.132). Conversely, GTR was associated with a significantly longer mPFS (NR vs 63.0 months, p = 0.007) and with a trend for longer mOS (NR vs 332.0 months, p = 0.146). In a multivariable analysis, GTR was associated with a significantly lower risk of disease progression, both in the entire cohort of PFE patients ( p = 0.016), and within the PFA subtype ( p = 0.013). Similarly, GTR was associated with a trend for better PFS within the PFB subtype. Conclusion: Our preliminary data on a real-life cohort of adult patients confirm the worse prognosis of STEs harbouring the ZFTA fusion and suggest an impact of the EOR among PFEs regardless of molecular subtypes. Larger populations of patients are needed to better define the role of treatment modalities within molecular subrogups. The study is still ongoing in a multicentric setting.